Altruísmo, solidariedade, idealismo... O que faz os estados ratifi carem tratados de direitos humanos? - Jomara de Carvalho Ribeiro (Revista Interdisciplinar de Direito, 2010)
International concern on human rights issues has been growing since 1945, when World War II ended. After the creation of the Organization of the United Nations (UN), members States adopted the Universal Declaration of Human Rights in 1948. Since then, several international binding treaties relating to human rights matters were signed and ra-tifi ed by States which compromised in taking those standards domestically, vis-à-vis their own nationals and foreigners who reside in their territories. But what are the reasons for such commitment if human rights standards limit State’s sovereign power? Th ere are some theories which try to explain States behavior towards human rights. Th ese theories discuss the relation between external and internal factors and the level of democracy within the country in order to explain States behavior. Th ey view States behavior by a cost/benefi t perspective. Brazil’s ratifi cation and accession to human rights treaties has intensifi ed since the government transition (from a military dictatorship to a democracy) in 1985. At that time new Brazilian government emphasized the importance of observance of human rights standards internally as well as a policy to improve Brazilian external image.